KINETICS OF A S.G. CAST IRON - Ioan Milosan (European Scientific Journal, ESJ, 2014)
The paper presents an application for calculating the kinetics parameters in the case of a phase transformation in solid state in A.D.I. S.G. grade. It is pointed out the influence of some factors (the temperature and the holding time at the isothermal level) on the phase transformation and properties in the studied cast iron. The kinetics of austenitization of S.G. Cast Iron, was described by the “Johnson-Mehl-Avrami” equation.